2012
DOI: 10.1371/journal.pone.0045576
|View full text |Cite
|
Sign up to set email alerts
|

Immune Phenotype and Body Condition in Roe Deer: Individuals with High Body Condition Have Different, Not Stronger Immunity

Abstract: An efficient immunity is necessary for host survival, but entails energetic costs. When energy is limited, immunocompetence and body condition should co-vary positively among individuals and, depending on body condition, individuals should allocate more either in innate immunity or in adaptive response. We tested whether immune phenotype depends on body condition in large mammals, using data from two contrasted populations of roe deer Capreolus capreolus in France. Roe deer living at Chizé, a forest with poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 27 publications
3
65
0
Order By: Relevance
“…Trois-Fontaines has been a consistently highly productive forest, whereas Chize´has been markedly food-limited in several years. Moreover, a recent immunological analysis supports the high energetic stress at Chize ( Gilot-Fromont et al 2012). at.…”
Section: Pathways Generating Long-lasting Cohort Effects On Adult Massmentioning
confidence: 76%
“…Trois-Fontaines has been a consistently highly productive forest, whereas Chize´has been markedly food-limited in several years. Moreover, a recent immunological analysis supports the high energetic stress at Chize ( Gilot-Fromont et al 2012). at.…”
Section: Pathways Generating Long-lasting Cohort Effects On Adult Massmentioning
confidence: 76%
“…Although the method was originally developed for avian species, it has recently been modified for mammals by using chicken erythrocytes as target cells62. After pipetting 25 μl of plasma in the wells of the first two columns of a U-shaped 96-well microtitre plate, 25 μl sterile PBS was added to the 2 nd –12 th columns.…”
Section: Methodsmentioning
confidence: 99%
“…Haemagglutination/haemolysis titers were given as the log 2 of the reciprocal of the highest dilution (i.e. lowest concentration) of plasma showing positive haemagglutination or haemolysis, respectively62104.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Gilot‐Fromont et al . () showed that body mass is associated with haematological parameters among roe deer. Therefore, haematological parameters should decrease with increasing age more strongly when analysed on an absolute scale than relative to body mass.…”
Section: Introductionmentioning
confidence: 99%